2013
DOI: 10.1080/03601234.2014.844600
|View full text |Cite
|
Sign up to set email alerts
|

A correlation between the fate and non-extractable residue formation of14C-metalaxyl and enzymatic activities in soil

Abstract: Extracellular, oxidative soil enzymes like monophenol oxidases and peroxidases play an important role in transformation of xenobiotics and the formation of organic matter in soil. Additionally, these enzymes may be involved in the formation of non-extractable residues (NERs) of xenobiotics during humification processes. To examine this correlation, the fate of the fungicide (14)C metalaxyl in soil samples from Ultuna (Sweden) was studied. Using different soil sterilization techniques, it was possible to differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Considering their characteristic surface properties and associated microenvironments, different PSFs most likely select for specifically adapted microbial entities in soil. Previous studies have revealed PSF-specific microbial activity, as indicated by measurements of soil enzymes (Stemmer et al, 1998 ; Kandeler et al, 2000 ; Marx et al, 2005 ), nitrogen mineralization, ammonification, nitrification and denitrification (Lensi et al, 1995 ; Nacro et al, 1996 ; Christensen and Olesen, 1998 ), methanogenesis (Zhang et al, 2007 ; Zheng et al, 2007 ), and sorption and mineralization of organic pollutants (Botterweck et al, 2014 ; Hemkemeyer et al, 2015 ). Furthermore, the abundance of a gene involved in phosphorous-cycling differed between PSFs (Luo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering their characteristic surface properties and associated microenvironments, different PSFs most likely select for specifically adapted microbial entities in soil. Previous studies have revealed PSF-specific microbial activity, as indicated by measurements of soil enzymes (Stemmer et al, 1998 ; Kandeler et al, 2000 ; Marx et al, 2005 ), nitrogen mineralization, ammonification, nitrification and denitrification (Lensi et al, 1995 ; Nacro et al, 1996 ; Christensen and Olesen, 1998 ), methanogenesis (Zhang et al, 2007 ; Zheng et al, 2007 ), and sorption and mineralization of organic pollutants (Botterweck et al, 2014 ; Hemkemeyer et al, 2015 ). Furthermore, the abundance of a gene involved in phosphorous-cycling differed between PSFs (Luo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%